(untitled) (World Bulletin of Social Sciences, 2024)
These proverbs are the object of constant study by linguists and historians, ethnographers from many fields of linguistics . Proverbs are an important studied object of text linguistics as a semantically and structurally complete text. Grammatically, proverbs are sentences that are considered a specific syntactic unit